Fungal–plant interaction: a pathogenic relationship between Ganoderma segmentatum sp. nov. and Vachellia nilotica - Umar, Aisha; Yuan, Wanlan; Lu, Junxing; Ameen, Fuad (Frontiers in Microbiology, 2024)
The diversity of Ganoderma remains largely unexplored, with little information available due to fungiphobia and the morphological plasticity of the genus. To address this gap, an ongoing study aims to collect and identify species with this genus using nuclear ribosomal DNA regions called the “Internal Transcribed Spacer” (ITS1-5.8S-ITS2 = ITS). In this study, a new species, Ganoderma segmentatum sp. nov., was discovered on the dead tree trunk of the medicinal plant, Vachellia nilotica. The species was identified through a combination of morpho-anatomical characteristics and phylogenetic analyses. This new species was closely related to Ganoderma multipileum, G. mizoramense, and G. steyaertanum, with a 99% bootstrap value, forming a distinct branch in the phylogenetic tree. Morphologically, G. segmentatum can be distinguished by its frill-like appearance on the margin of basidiome. Wilt or basal stem rot, a serious disease of trees caused by Ganoderma species and V. nilotica, is brutally affected by this disease, resulting in substantial losses in health and productivity. This Ganoderma species severely damages V. nilotica through deep mycelial penetration in the upper and basal stems of the host species. Pathogenic observational descriptions of G. segmentatum on dead tree trunks showed the exudation of viscous reddish-brown fluid from the basal stem portion, which gradually extended upward. Symptoms of this disease include decay, stem discoloration, leaf drooping, and eventual death, which severely damaged the medicinal tree of V. nilotica.